Genomics of Preterm Birth—Evidence of Association and Evolving Investigations - McPherson, Jessica A.; Manuck, Tracy A. (American Journal of Perinatology, 2016)
Preterm birth (PTB) is a large public health problem in the United States and worldwide. There is a clear genetic component to the pathogenesis of PTB, as evidenced by twin studies, heritability studies, and investigations from large population databases. Although numerous single nucleotide polymorphisms have been associated with PTB, results have been inconsistent and overall disappointing. With recent advances in genetic technology, investigations are moving beyond simple, more traditional candidate gene studies, and have expanded to encompass more exploratory analyses using high-throughput genetic techniques. Care should be taken to consider the potential impact of fetal genotype, the environment, and gene–drug interactions (pharmacogenomics) in addition to maternal genotype. Future research should capitalize on evolving analytic techniques, including pathway analyses and correlation of genetic and functional data to optimize discovery, increase knowledge regarding prematurity pathogenesis, and begin to develop novel therapeutic strategies.
Keywords: preterm birth; genetics; phenotype; fetal genotype; maternal genotype; heritability